Population size interacts with reproductive longevity to shape the germline mutation rate - Luke Zhu; Annabel Beichman; Kelley Harris (Proceedings of the National Academy of Sciences, 2025)
Mutation rates vary across the tree of life by many orders of magnitude, with fewer mutations occurring each generation in species that reproduce quickly and maintain large effective population sizes. A compelling explanation is that large effective population sizes facilitate selection against weakly deleterious “mutator alleles” such as variants that modulate cell division or interfere with the molecular efficacy of DNA repair. However, while the fidelity of a single cell division largely determines microorganisms’ mutation rates, the relationship of the mutation rate to the molecular determinants of DNA damage and repair is more complex in multicellular species with long generation times. Since long generations leave more time for mutations to accrue each generation, we posit that a long generation time likely amplifies the fitness consequences of any damage agent or DNA repair defect that creates extra mutations in the spermatogonia or oocytes. This leads to the counterintuitive prediction that the species with the highest germline mutation rates per generation are also the species with most effective mechanisms for avoiding and repairing mutations in their reproductive cells. Consistent with this, we show that mutation rates in the reproductive cells are inversely correlated with generation time; in contrast, the number of germline mutations that occur during prepuberty development trends weakly upward as generation time increases. Our results parallel recent findings that the longest-lived species have the lowest mutation rates in adult somatic tissues, potentially due to selection to keep the lifetime mutation load below a harmful threshold.